Indoor air quality - Digital-2000 (Firm) (Stafford, TX : Digital-2000, 2009)
Topics covered in this safety video include: health issues - long term health effects including respiratory diseases and cancer, immediate effects including irritation of the eyes, nose and throat, headaches, dizziness, and fatigue, asthma, hypersensitivity pneumonitis, and humidifier fever, dry or burning mucous membranes in the nose, eyes and throat, sneezing, stuffy or runny nose, fatigue or lethargy, headache, dizziness, nausea, irritability, and forgetfulness, indoor air pollution costs including direct medical costs for people whose health is affected by poor indoor air quality, lost productivity from absence due to illness, decreased efficiency on the job, and materials and equipment damage due to exposure to indoor air pollutants, Safe Drinking Water Act (SDWA), HVAC systems, indoor air quality problems, Federal Insecticide, Fungicide, and Rodenticide Act, and exposure to tobacco smoke.
DVD format.
Keywords: Indoor air pollution -- Health aspects; Industrial safety